Smooth or sticky? An analysis of service variability - Jianlan Zhong; Zhibin Lin; Fu Jia; Tobias Schoenherr (Humanities & Social Sciences Communications)
Abstract This study examines the impact of service variability on customer-perceived service quality across various stages of the customer experience journey. Through a behavioral experiment, the findings reveal that the overall perceived service quality is influenced by the interplay between the mean and variability of service quality. Positive variability can elevate service quality at specific phases, yet its impact is contingent on the average service level. Moreover, the order in which positive and negative variability occur contributes to shaping overall perception. The research also indicates that new guests are more susceptible to variability than repeat customers. This study enriches the debate between consistency and unpredictability in service offerings, providing valuable insights to refine tourism service design and enhance overall customer satisfaction.